2020
DOI: 10.1111/trf.15693
|View full text |Cite
|
Sign up to set email alerts
|

How do you… decide which platelet bacterial risk mitigation strategy to select for your hospital‐based transfusion service?

Abstract: The United States Food and Drug Administration Final Guidance for Industry titled, “Bacterial Risk Control Strategies for Blood Collection Establishments and Transfusion Services to Enhance the Safety and Availability of Platelets for Transfusion” provides nine strategies for platelet bacterial risk mitigation. Even if it is assumed all strategies are comparable in terms of safety and efficacy, the decision of which to implement remains challenging. Some additional factors that warrant evaluation before select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
5
0
4
Order By: Relevance
“…According to the 2017 NBCUS, only 6.1% of reporting hospitals were transfusing PR PLT 1 . There has, however, been a trend toward increased utilization, which is expected to continue with the implementation of the FDA guidance on bacterial mitigation, 13 and the 2021 AABB Platelet Survey showed that 62% of responding hospitals selected PR PLT as their preference for meeting the guidance 23 . A number of studies have demonstrated that PR PLT are clinically equivalent to conventionally processed platelet concentrates (CONV PLT) for the prevention of bleeding events 24–27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the 2017 NBCUS, only 6.1% of reporting hospitals were transfusing PR PLT 1 . There has, however, been a trend toward increased utilization, which is expected to continue with the implementation of the FDA guidance on bacterial mitigation, 13 and the 2021 AABB Platelet Survey showed that 62% of responding hospitals selected PR PLT as their preference for meeting the guidance 23 . A number of studies have demonstrated that PR PLT are clinically equivalent to conventionally processed platelet concentrates (CONV PLT) for the prevention of bleeding events 24–27 .…”
Section: Introductionmentioning
confidence: 99%
“…The United States Food and Drug Administration (US FDA) guidance Bacterial Risk Control Strategies for Blood Collection Establishments and Transfusion Services to Enhance the Safety and Availability of Platelets for Transfusion , 12 released in September 2019 outlines the current requirements to further enhance the safety of platelet products. The guidance delineates one‐step strategies that include pathogen‐reduction technology (PRT) and large volume delayed sampling options, while two‐step strategies include a secondary culture or point‐of‐issue rapid testing following a primary culture 12, 13 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, other methods may need to be explored when prolonging the shelflife of PC to keep a balance between safety and efficacy. For instance, large volume delayed sampling (LVDS) was found to be more appropriate when prolonging the storage life by up to 7 days and is more cost-effective than pathogen reduction methods [35,50,51]. Consequently, even though there is increased bacterial proliferation during prolonged storage, the risk of a TTBI or STR between Day 5 and Day 10 is analogous to the detection or reduction of bacterial contamination [36,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…In the survey, 7 of the 35 (20%) sites use pathogen‐reduced platelet transfusions with their neonatal and/or pediatric patient populations. This may reflect regional variability in the ability to obtain these products, unfamiliarity surrounding the utility and safety profile in this patient population, possible increased cost, or the impact by the hospital's decision on the use of PR products 27 . Over time, this is likely to change, and because time has elapsed since the survey was completed, it is possible that some changes in practice have already occurred.…”
Section: Discussionmentioning
confidence: 99%